NOTES ON SUPPLETION IN THE CONTEMPORARY ROMANIAN LANGUAGE - ROMAN, Diana-Maria (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Notes on Suppletion in the Contemporary Romanian Language. Insofar as the meanings of suppletion are concerned, we should delineate two working coordinates, both of which acknowledge the “total change of the radical”: the total variation of the root without affecting the flective (in the case of the verbs a fi, to be, and a lua, to take), and the total variation of the root with the absorption of the flective (in the case of personal pronouns proper and reflexive pronouns), the lexemes becoming nonflexible. Once the absence of the flective is accepted, gender, number and case are actualized in the form of non-flectional grammatical categories, as proved, where possible, by its substitution, in the given position, with a flexible pronoun and by the flectional syntagmatic grammatical agreement of a flexible adjectival with these categories. When they are subordinate terms, in the absence of a preposition/ prepositional phrase, these lexemes are subordinated through the adherence-relateme. Rezumat. Observaţii asupra supletivismului limbii române contemporane. În ceea ce priveşte accepţiunile supletivismului, trebuie delimitate două coordonate de lucru având, ca notă comună, „schimbarea totală a radicalului”: variaţia totală a radicalului fără afectarea flectivului, în această situaţie, fiind verbele a fi şi a lua, variaţia totală a radicalului cu absorbirea flectivului, situaţia pronumelor personale propriu-zise şi reflexive, lexemele devenind neflexibile. Odată acceptată absenţa flectivului, genul, numărul şi cazul se actualizează sub forma categoriilor gramaticale aflectivale, dovada realizând-o, acolo unde se poate, substituirea în poziţia dată cu un pronume flexibil, acordul gramatical sintagmatic flectival al unui adjectival flexibil cu acestea. Când sunt termeni subordonaţi, în absenţa prepoziţiei/locuţiunii prepoziţionale, respectivele lexeme se subordonează prin relatemul-aderenţă. Cuvinte-cheie: supletivism, radical, variaţie totală, flexiune, flectiv, categorie gramaticală aflectivală